2018
DOI: 10.1111/bph.14361
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein arginine methyltransferase 3 activity selectively impairs liver X receptor‐driven transcription of hepatic lipogenic genes in vivo

Abstract: Background and PurposeAgonists for the liver X receptor (LXR) are considered promising therapeutic moieties in cholesterol‐driven diseases by promoting cellular cholesterol efflux pathways. However, current clinical application of these agents is hampered by concomitant LXR‐induced activation of a lipogenic transcriptional network, leading to hepatic steatosis. Recent studies have suggested that protein arginine methyltransferase 3 (PRMT3) may act as a selective co‐activator of LXR activity. Here, we verified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…However, the involvement of histone arginine methylation in the lineage commitment of MSCs remains unclear. PRMT3 catalyzes asymmetric dimethylation of H4R3 23,48,49 . We confirmed that H4R3 is a substrate of PRMT3 in MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the involvement of histone arginine methylation in the lineage commitment of MSCs remains unclear. PRMT3 catalyzes asymmetric dimethylation of H4R3 23,48,49 . We confirmed that H4R3 is a substrate of PRMT3 in MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to explore the detailed mechanism of how PRMT3 affects the function of osteoclasts and thus regulates the process of bone resorption. Joya et al found that SGC707 treatment impairs the hepatic lipogenesis due to administration of LXR agonists as therapeutic agents for cholesterol-driven diseases in an in vivo animal study 49 . Our study revealed the effect of SGC707 on bone metabolism, which should be taken into consideration for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…The first described inhibitor of PRMT3, compound 1, exhibited allosteric binding and showed promise as an emerging therapy [ 129 ]. SGC707 was an analog that demonstrated improved selectivity and potency over the parent compound in pre-clinical testing of adenocarcinoma ( Table 2 ) [ 45 , 130 ].…”
Section: Prmt Inhibition and Clinical Applicationsmentioning
confidence: 99%
“…In the mouse models of alcohol induced liver injury, PRMT1 protect hepatocytes from oxidative stress response [30 , 31] . PRMT3 is involved in hepatic lipogenesis by interacting with LXRα, and palmitic acid treatment induces PRMT3 translocation to the nucleus accompanied by increased transcriptional activity of LXRα in mouse models of NAFLD [32] , [33] , [34] . PRMT6 promotes fasting-induced activation of the gluconeogenic program dependent on CRTC2, and couples glucose availability with mitochondria biogenesis by mediating SIRT7 methylation [35 , 36] .…”
Section: The Role Of Prmts In Benign Liver Diseasesmentioning
confidence: 99%